The Encke comet impact/airburst and the Younger Dryas Boundary: Testing the impossible hypothesis (YDIH) - Mahaney, William C.; Somelar, Peeter (Geologos, 2024)
Many have tagged the Younger Dryas Impact Hypothesis (YDIH), a supposition, lacking convincing evidence in support. The core of criticism lies squarely on uniformitarianism, that is, uniform processes moving uniformly with no room for catastrophic events, specifically cosmic catastrophic forces. Beyond philosophically based aversion to the YDIH, specific criticism comes from megafauna and archaeologic corners, related to the near coeval disappearance of specific Late Pleistocene species on the one hand, and relation to disruption and temporary disappearance of the Clovis people et al. on the other. The Younger Dryas geologic paradigm, originally in place with meltwater release into the Atlantic in tow, attention slowly drifted to explanation of an innocuous looking, thin ( 1-3 cm), black sediment bed found in lacustrine and fluvial deposits of the American southwest, and other intercontinental places. Thus, with thin dark beds of Gubbio in mind, the quest to explain black mat (BM) beds took on a cosmic aspect, one with growing, supporting evidence on several continents. The impossible hypothesis, now the probable explanation of the Younger Dryas climatic reversal, is at center stage, set at 12.8 ka, with a burgeoning corpus of evidence its cornerstone.